Results of fishery for pink salmon Oncorhynchus gorbuscha in Primorye Region and hydrometeorological conditions in the Japan Sea in 2023 - A. V. Lysenko; A. A. Nikitin; Т. A. Shatilina; E. I. Barabanshchikov (Известия ТИНРО, 2024)
Catch and distribution of pink salmon in the Primorye fishing subzone are compared for 2000–2023. Dynamics of the spawning run of pink salmon in 2023 is considered in detail. Commercial landing for weak odd-year broodline of this species in Primorye has increased to 1.5.103 t for the first time in the 21 century, whereas has de- creased in Khabarovsk Region. Such redistribution of pink salmon in 2023 occurred on the background of anomalous environmental conditions in the northern Japan Sea and Tatar Strait. Long-term patterns in variability of hydrometeorological parameters are analyzed and a forecast of their influence on anadromous migration of pink salmon in the Japan Sea is developed for 2024−2025.